Increased absolute lymphocyte count, increased absolute neutrophil count and low platelet to lymphocyte ratio as predicting factors in the superior disease control of refractory/relapsing gynecologic malignancies with anti PD-1 therapy: 10 years of experience in a single institution - Wan-Ju Lee; Yi-Lun Wang; Hsiu-Huei Peng; Cheng-Tao Lin (Elsevier, 2023)
Objective: Immune checkpoint inhibitors are rapidly being used in solid and hematologic malignancies, including gynecologic cancers. The high mortality and relapsing rates of advanced gynecologic malignancies remain a challenging issue. This study aimed to identify the predicting factors associated with survival prognosis and disease control in patients with refractory/relapsing (R/R) gynecologic malignancies receiving anti PD-1 therapy. Materials and methods: We retrospectively reviewed the medical records of 49 patients diagnosed with R/R gynecologic malignancies between July 2012 and June 2019 in Chang Gung Memorial Hospital, Taiwan. Among the 49 patients, 6 were excluded due to incomplete medical records or not receiving anti PD-1 therapy. The remaining 43 patients were further divided into responsive and non-responsive groups according to disease control for predicting prognostic factor analysis. Results: For the 43 cases, the median age at diagnosis and disease follow-up length were 54 years and 29 months, respectively. Among them, 23 (53%) were categorized into the responsive group, and the remaining 20 (47%) were categorized into the non-responsive group. The mortality rates were 17% and 25% in the responsive and non-responsive groups, respectively. The responsive group had significantly higher absolute lymphocyte count (ALC), higher absolute neutrophil count (ANC) and low platelet to lymphocyte ratio (PLR) than the non-responsive group. A superior long-term survival trend was also observed in the responsive group, but the difference was not statistically significant. Conclusions: This study reinforced the hypothesis that high ALC, high ANC and low PLR are associated with superior disease control in patients with R/R gynecologic malignancies receiving anti PD-1 therapy.